Exploring undergraduate students awareness of internal shariah auditing in Malaysia - Azam Abdelhakeem Khalid (Tanjong Malim, 2019)
Exploring undergraduate students awareness of internal shariah auditing in Malaysia by Azam Abdelhakeem Khalid